2014
DOI: 10.1002/jaba.123
|View full text |Cite
|
Sign up to set email alerts
|

Using instructive feedback to teach category names to children with autism

Abstract: We evaluated the effects of instructive feedback (IF) on the emergence of spoken category names with 2 children who had been diagnosed with autism. IF stimuli were presented during listener discrimination training and consisted of presenting the category name associated with each target stimulus. Results suggest that participants acquired the speaker relations in the absence of prompting and reinforcement. Clinical implications and future research on the use of IF as a teaching procedure for children with auti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 6 publications
2
30
0
2
Order By: Relevance
“…Even though several studies have used vocal IF related to the primary targets (e.g., Leaf et al, ; Loughrey et al, ; Tullis et al, ), our study is the first to test for intraverbals related to the primary and secondary targets. Our findings should be interpreted with caution, as we incorporated IF in the context of a previously mastered skill, which is not considered standard practice (Reichow & Wolery, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though several studies have used vocal IF related to the primary targets (e.g., Leaf et al, ; Loughrey et al, ; Tullis et al, ), our study is the first to test for intraverbals related to the primary and secondary targets. Our findings should be interpreted with caution, as we incorporated IF in the context of a previously mastered skill, which is not considered standard practice (Reichow & Wolery, ).…”
Section: Discussionmentioning
confidence: 97%
“…Variations of IF have been used in other disciplines and may be referred to as mapping (Carey & Bartlett, ) or vocal expansions (Scherer & Olswang, ). Results across a variety of studies suggest that learners may acquire both the primary and secondary targets, though responding was only explicitly required for the primary target (e.g., Delmolino, Hansford, Bamond, Fiske, & LaRue, ; Gast, Doyle, Wolery, Ault, & Kolenda, ; Leaf et al, ; Loughrey, Betz, Majdalany, & Nicholson, ; Reichow & Wolery, ; Tullis, Frampton, Delfs, & Shillingsburg, ; Vladescu & Kodak, ). Secondary targets have been presented during the antecedent (Vladescu & Kodak, ) or consequence portions of the trial (Delmolino et al, ), and may or may not have a relationship to the primary target (Gast et al, ).…”
mentioning
confidence: 99%
“…After teaching sessions, the modeled skills are probed under extinction. Learners with autism spectrum disorder (ASD) have acquired secondary targets without explicit training by using instructive feedback (e.g., Loughrey, Betz, Majdalany, & Nicholson, 2014;Vladescu & Kodak, 2013).Much of the research has focused on teaching secondary targets that are expansions of the trained targets (Nottingham, Vladescu, & Kodak, 2015). That is, the trained and secondary targets are similar or related skills.…”
mentioning
confidence: 99%
“…After teaching sessions, the modeled skills are probed under extinction. Learners with autism spectrum disorder (ASD) have acquired secondary targets without explicit training by using instructive feedback (e.g., Loughrey, Betz, Majdalany, & Nicholson, 2014;Vladescu & Kodak, 2013).…”
mentioning
confidence: 99%
“…Research fi ndings have shown that acquisition is enhanced with short (e.g., 2-s to 3-s) versus long (e.g., 10-s to 20-s) it is (e.g., Koegel, Dunlap, & Dyer, 1980 ;Majdalany et al, 2014 ). Some research, however, also suggests advantages to presenting additional instructional stimuli during ITIs (e.g., Loughrey, Betz, Majdalany, & Nicholson, 2014 ;Reichow & Wolery, 2011 ;Vladescu & Kodak, 2013 ). With this approach, the therapist inserts supplementary information immediately prior to or following instructional trials, with no response required of the learner.…”
Section: Intertrial Interval (Iti)mentioning
confidence: 93%